Pengembangan Website E-commerce menggunakan Payment Gateway Midtrans (Studi Kasus : Butik Kebaya Iffah) - Velia Wilda Ifanah; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Kebaya Iffah boutique is a brand that is engaged in the fashion business, which sells various kinds of self-produced kebaya. The boutique business process is still carried out by two methods, namely offline coming directly and online through social media to promote products. Found problems with online methods that are considered less effective and safe for customers to make transactions and have not had a big promotional impact, the mechanism for buying custom products, customers must come to the store Payment processing, many requests for payment method choices, also for admins still checking payment status manually and not in real-time. So from the existing problems, the Kebaya Iffah Boutique E-commerce Website was developed which was integrated using the midtrans payment gateway. System development is carried out using the waterfall method. The results of this study obtained 18 different functional needs and actors. The distinguishing feature of e-commerce can be done by customizing the size of the kebaya. This system is built using the codeigniter framework and boostrap as a system development aid. After being designed and implemented, testing is carried out using the black box testing method with 100% valid results, which means the function is running well, compatibility testing which means the system can run in different environments, and user acceptance testing (UAT) by obtaining a percentage result of 90.3 % which means the system is made according to the user's needs and is accepted with very agree results.